2012
DOI: 10.1089/ars.2011.4264
|View full text |Cite
|
Sign up to set email alerts
|

Penaeus monodonThioredoxin Restores the DNA Binding Activity of Oxidized White Spot Syndrome Virus IE1

Abstract: WSSV's pathogenicity is enhanced by the virus' use of host Trx to rescue the DNA binding activity of WSSV IE1 under oxidizing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Indeed, WSSV IE1 has already been found to exhibit DNA-binding and transactivation activities, indicating that it has a role as a transcription factor (6). Although the C55 residue and the C2H2 zinc finger motif important for DNA binding (14) are conserved between these two proteins (Fig. 1), whether WSV056 has a similar transcriptional regulation function remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, WSSV IE1 has already been found to exhibit DNA-binding and transactivation activities, indicating that it has a role as a transcription factor (6). Although the C55 residue and the C2H2 zinc finger motif important for DNA binding (14) are conserved between these two proteins (Fig. 1), whether WSV056 has a similar transcriptional regulation function remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The biological significance of IE1 during WSSV infection was demonstrated by RNA interference experiments which revealed that depletion of IE1 strongly inhibits the replication of WSSV (11). A recent report showed that the shrimp thioredoxin PmTrx can bind to IE1 and restore its DNAbinding activity under oxidizing conditions, indicating a role for IE1 in WSSV pathogenicity (14). However, since little is known about the targets (proteins or genes) of IE1, how this viral protein functions during infection remains unknown.…”
mentioning
confidence: 99%
“…However, although an excess of oxidizing species destroys a cell’s macromolecules, the oxidative stress that is induced in response to virus infection benefits the host by limiting virus replication 1 2 . For example, in a previous study, we found that the DNA binding activity of the important WSSV transcriptional regulator IE1 was inhibited under oxidative conditions 3 .…”
mentioning
confidence: 83%
“…Curiously, however, although large quantities of oxidants are produced by shrimp hemocytes after challenge with Vibrio spp. 4 5 , when shrimp are infected by white spot syndrome virus (WSSV), ROS are only detected at the very late stages of infection (24 hours post injection), while at the viral replication stage (~12 hpi) the ROS levels are actually lower in the WSSV infected shrimp than in the controls 3 6 7 8 . This suggests either that for some reason the host is not producing ROS in response to WSSV infection or else that WSSV is deploying effective countermeasures against the host’s ROS defenses in order to achieve replication.…”
mentioning
confidence: 99%
“…A previous study reported that IE1 interacted with a retinoblastoma (Rb)-like protein in the shrimp Litopenaeus vannamei and modulated the cell cycle (G1/S transition) through the Rb-E2F pathway (Ran et al., 2013). Another study also showed that in the shrimp Penaeus monodon the thioredoxin protein PmTrx, an important redox regulator, was able to bind to IE1 and restore its DNA-binding activity under oxidizing conditions, indicating a role for IE1 in WSSV pathogenicity (Huang et al., 2012). In addition, WSSV infection was shown to activate several host signaling pathways, and the host transcription factors of these signaling pathways, such as STAT, NF-κB, and AP-1, enhanced the transcription of IE1 (Huang et al., 2010, Yao et al., 2015, Yao et al., 2016).…”
Section: Introductionmentioning
confidence: 99%